Immune Reconstitution After Gene Therapy Approaches in Patients With X-Linked Severe Combined Immunodeficiency Disease - Blanco, Elena; Izotova, Natalia; Booth, Claire; Thrasher, Adrian James (Frontiers in Immunology, 2020)
X-linked severe immunodeficiency disease (SCID-X1) is an inherited, rare and life-threating disease. The genetic origin is a defect in the interleukin 2 receptor γ chain (IL2RG) gene and patients are classically characterized by absence of T and NK cells, as well as presence of partially-functional B cells. Without any treatment the disease is usually lethal during the first year of life. The treatment of choice for these patients is hematopoietic stem cell transplantation, with an excellent survival rate (>90%) if an HLA-matched sibling donor is available. However, when alternative donors are used, the success and survival rates are often lower. Gene therapy has been developed as an alternative treatment initially using γ-retroviral vectors to correct the defective γ chain in the absence of pre-conditioning treatment. The results were highly promising in SCID-X1 infants, showing long-term T-cell recovery and clinical benefit, although NK and B cell recovery was less robust. However, some infants developed T-cell acute lymphoblastic leukemia after the gene therapy, due to vector-mediated insertional mutagenesis. Consequently, considerable efforts have been made to develop safer vectors. The most recent clinical trials using lentiviral vectors together with a low-dose pre-conditioning regimen have demonstrated excellent sustained T cell recovery, but also B and NK cells, in both children and adults. This review provides an overview about the different gene therapy approaches used over the last 20 years to treat SCID-X1 patients, particularly focusing on lymphoid immune reconstitution, as well as the developments that have improved the process and outcomes.